Ancaman Keselamatan dan Kenyamanan Lingkungan Hidup di Sekitar Area Pembuangan Sampah: Studi Kasus TPST Bantar Gebang - Khansa, Shabiika; Tantri, Kusuma; Safitri, Desy (Jurnal Ekologi, Masyarakat dan Sains, 2024)
The increasing volume of waste is now a new problem that needs to be solved. This research aims to determine the threat of safety and environmental comfort around the waste disposal area, specifically at the Bantar Gebang Integrated Waste Management Site. The method used in this research is a literature study obtained from the results of literature studies sourced from journals, literature, publications, and other relevant sources. The results of this study can be a recommendation to prevent various threats to the safety and comfort of the environment around the Integrated Waste Management Site that have the potential to threaten the sustainability of the environment and the living conditions of the surrounding community.